1996
DOI: 10.1038/ki.1996.474
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of oxidation in LDL-induced collagen gene regulation in mesangial cells

Abstract: Oxidized low-density lipoprotein (Ox-LDL) is present in the lesions of focal segmental glomerulosclerosis (FSGS), but the role of Ox-LDL in the disease process is not clear. Recent studies have shown that LDL stimulates the type IV collagen mRNA expression in cultured mesangial cells. Thus, we examined whether oxidative stress is responsible for the stimulation of LDL-induced collagen gene expression in cultured human mesangial cells (HMCs). When quiescent HMCs were exposed to serum-free media containing LDL f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 53 publications
4
30
0
Order By: Relevance
“…Ujihara et al (52) reported significantly higher serum oxLDL levels only in diabetics with macroalbuminuria, compared to normoalbuminuric and microalbuminuric patients and healthy controls (16.8±7.5 vs. 13.7±3.9 vs. 12.8±3.9 vs. 12.5±4.2 U/mL, respectively). These findings may suggest an association between oxLDL and progression of renal dysfunction in diabetic patients, which may also be corroborated by the fact that oxLDL stimulates collagen IV production in mesangial cells (53).…”
Section: Discussionsupporting
confidence: 54%
“…Ujihara et al (52) reported significantly higher serum oxLDL levels only in diabetics with macroalbuminuria, compared to normoalbuminuric and microalbuminuric patients and healthy controls (16.8±7.5 vs. 13.7±3.9 vs. 12.8±3.9 vs. 12.5±4.2 U/mL, respectively). These findings may suggest an association between oxLDL and progression of renal dysfunction in diabetic patients, which may also be corroborated by the fact that oxLDL stimulates collagen IV production in mesangial cells (53).…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies in renal mesangial and tubular cells grown in culture have shown that incubation of these cells with low density lipoprotein or very low density lipoprotein causes upregulation of growth factors, including TGF-␤ and plateletderived growth factor (36), plasminogen activator inhibitor 1 (37,38), extracellular matrix proteins (36,39), pro-inflammatory cytokines including interleukins and tumor necrosis factor ␣ (36), adhesion molecules including monocyte chemoattractant protein-1 (MCP-1), intercellular adhesion molecule 1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) (40,41), and lipid peroxidation and glycoxidation (42). Our studies in vivo indicate that accumulation of renal triglycerides in streptozotocin-treated diabetic rats and SREBP-1a transgenic mice causes increased expression of TGF-␤ and VEGF as well as collagen and fibronectin, resulting in glomerulosclerosis and proteinuria.…”
Section: Srebp-1 Modulates Renal Lipid Metabolism In Diabetesmentioning
confidence: 99%
“…10,13 Through this, 3 important consequences arise: 1) antigen formation 13,14 ; 2) loss of affinity to the normal LDL receptor (Apo B/E receptor) 14 ; and 3) cellular uptake of ox-LDL by scavenger receptors, resulting in foam cell formation. 12,14,15 Except for its role in foam cell formation, growing interest has developed in oxLDL effects on cell viability, regulation of gene expression, monocyte and lymphocyte recruitment, and macrophage propagation. 16 Recent evidence suggests that oxLDL might exert a direct stimulatory effect on the synthesis of DNA and connective tissue components in vascular smooth muscle cells and mesangial cells.…”
mentioning
confidence: 99%
“…8 Lipid-peroxidative modification of LDL to oxidized lowdensity lipoproteins (oxLDL) is known to be the crucial event in atherosclerosis 3,9,10 and certain forms of glomerulosclerosis. 11,12 Malondialdehyde (MDA) and 4-hydroxynonenal, which represent the most common aldehydes produced during lipid peroxidation, form adducts with the apoprotein moiety of LDL. 10,13 Through this, 3 important consequences arise: 1) antigen formation 13,14 ; 2) loss of affinity to the normal LDL receptor (Apo B/E receptor) 14 ; and 3) cellular uptake of ox-LDL by scavenger receptors, resulting in foam cell formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation